FOREIGN INVESTMENT AND ITS IMPACT ON INDIA’S FOREIGN TRADE: AN ECONOMIC ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
India is rich in natural resources and but poor in investment. This is the general trend. This trend leads to low economic development. Moreover, in order to remove poverty and unemployment India needs more capital. However the domestic supply of capital is lesser than the demand for capital for greater level of economic growth. Here foreign investment assumes importance and it is also necessary to use it effectively and efficiently for higher growth rate. This study tries to investigate the impact of foreign direct investment on foreign trade in India and further attempt to suggest policies for effective use of foreign direct investment for foreign trade as well as economic development.This analytical study is taking Foreign Direct Investment and Foreign Trade like exports and imports and Gross Domestic Products. This study reveals that to find out the causal relationship between various trade variables such as GDP, export and import and FDI, regression analysis analysis is used and the results shows that FDI and GDP and exports has greater relationship. This means FDI causes increase in GDP and India’s exports. But the India’s foreign imports are not influenced by the FDI.